A baseline investigation of phytoplankton pigment composition in contrasting coastal ecosystems of north-western Bay of Bengal. (November 2020) - Srichandan, Suchismita; Baliarsingh, Sanjiba Kumar; Lotliker, Aneesh Anandrao; Prakash, Satya; Samanta, Alakes; Sahu, Kali Charan
Abstract: A baseline investigation of the chromatographic characterization of phytoplankton pigments with complementing microscopy was conducted in Mahanadi estuary, Chilika lagoon, and coastal waters off Gopalpur along the east coast of India. Marker pigments specific to different phytoplankton groups have been discerned in these contrasting coastal ecosystems. A total of 16 phytoplankton pigments were identified. Irrespective of seasons, Chilika lagoon was characterized by a high concentration of zeaxanthin, indicating the predominance of picocyanobacteria. Zeaxanthin and fucoxanthin were the major diagnostic pigments in Mahanadi estuary during monsoon and other seasons, respectively. In coastal waters off Gopalpur, algal blooms resulted in a higher concentration of fucoxanthin during pre-monsoon and monsoon season. The pigment ratios were comparatively higher for Chilika lagoon than for Mahanadi estuary and off Gopalpur, irrespective of seasons. The present study highlights the advantages of the chromatography technique in identifying small-sized phytoplankton in coastal ecosystems in comparison to conventional microscopy. Highlights: Baseline study of phytoplankton pigment composition in contrasting coastal ecosystems of north-western Bay of Bengal Chromatographic evidence on the existence of cryptophytes, prymnesiophytes, and picocyanobacteria in the study regions Higher pigment diversity in lagoon in comparison to estuary and coastal water Chromatographic substantiation of pre-monsoon bacillariophyta-dinophyta bloom